2018
DOI: 10.3389/fbioe.2018.00159
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative Production of N-Methylglutamate From Glycerol by Recombinant Pseudomonas putida

Abstract: N-methylated amino acids are present in diverse biological molecules in bacteria, archaea and eukaryotes. There is an increasing interest in this molecular class of alkylated amino acids by the pharmaceutical and chemical industries. N-alkylated amino acids have desired functions such as higher proteolytic stability, enhanced membrane permeability and longer peptide half-lives, which are important for the peptide-based drugs, the so-called peptidomimetics. Chemical synthesis of N-methylated amino acids often i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…Many studies deal with the heterologous production by P. putida KT2440. Production of biosurfactants, such as hydroxyalkanoyloxy alkanoates (HAA), mono-rhamnolipids, and di-rhamnolipids (Tiso et al, 2017;Wittgens et al, 2017, terpenoids (zeaxanthin and β-carotene) (Beuttler et al, 2011;Loeschcke et al, 2013), amino acid-derived compounds (e.g., phenazines) (Schmitz et al, 2015b), polyketides/nonribosomal peptides (e.g., flaviolin, prodigiosin) (Gross et al, 2006;Loeschcke et al, 2013;Domröse et al, 2015), and Nmethylglutamate (Mindt et al, 2018) was demonstrated. These examples show how diverse the production spectrum in P. putida KT2440 can be.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies deal with the heterologous production by P. putida KT2440. Production of biosurfactants, such as hydroxyalkanoyloxy alkanoates (HAA), mono-rhamnolipids, and di-rhamnolipids (Tiso et al, 2017;Wittgens et al, 2017, terpenoids (zeaxanthin and β-carotene) (Beuttler et al, 2011;Loeschcke et al, 2013), amino acid-derived compounds (e.g., phenazines) (Schmitz et al, 2015b), polyketides/nonribosomal peptides (e.g., flaviolin, prodigiosin) (Gross et al, 2006;Loeschcke et al, 2013;Domröse et al, 2015), and Nmethylglutamate (Mindt et al, 2018) was demonstrated. These examples show how diverse the production spectrum in P. putida KT2440 can be.…”
Section: Discussionmentioning
confidence: 99%
“…These processes differ regarding the substrate spectra of the involved enzymes. For example, anthranilate N-methylation described here as well as N-methylglutamate production established in Pseudomonas putida using N-methylglutamate synthase and γ-glutamylmethylamide synthetase of the methylamine assimilation pathway of Methylobacterium extorquens [13] have narrow substrate spectra (e.g., GMAS from Methylovorus mays also forms γ-glutamylethylamide, also known as theanine [69]) compared with N-alkylation using the imine reductase DpkA of Pseudomonas putida [12]. Several methylated or ethylated amino acids could be produced by C. glutamicum using the wild-type or a mutant version of DpkA and either MMA or ethylamine as substrates [14,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Fermentation processes using simple mineral salts media have been developed for three different routes for de novo production of N -alkylated amino acids. Two metabolic engineering strategies for reductive alkylamination of 2-oxo acids with monomethylamine that either make use of a C1-assimilation pathway present in methylotrophic bacteria [ 13 ] or of the imine reductase DpkA [ 14 ] have been established. S -Adenosyl- l -methionine (SAM)-dependent methylation of aromatic amino acids by N -methyltransferases has also been described [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, sustainable fermentative production of N -methylated amino acids was established in 2018 using two independent pathways. Pathway interception of the C1 assimilation pathway of Methylobacterium extorquens and implementation of the first two genes coding for γ-glutamylmethylamide synthetase and N -methylglutamate synthase enabled glycerol-based production of N -methylglutamate in Pseudomonas putida KT2440 (Mindt et al, 2018b). The second pathway for production of N -methylated amino acids exploited the side activity of the imine reductase DpkA from Pseudomonas putida .…”
Section: Introductionmentioning
confidence: 99%